Species-specific synergistic effects of two plant growth-Promoting microbes on green roof plant biomass and photosynthetic efficiency - Xie, Long; Lehvävirta, Susanna; Timonen, Sari; Kasurinen, Jutta; Niemikapee, Juhamatti; Valkonen, Jari P. T. (PLOS ONE, 2019)
Rhizophagus irregularis, an arbuscular mycorrhizal fungus, and Bacillus amyloliquefaciens, a bacterium, are microorganisms that promote plant growth. They associate with plant roots and facilitate nutrient absorption by their hosts, increase resistance against pathogens and pests, and regulate plant growth through phytohormones. In this study, eight local plant species in Finland (Antennaria dioica, Campanula rotundifolia, Fragaria vesca, Geranium sanguineum, Lotus corniculatus, Thymus serpyllum, Trifolium repens, and Viola tricolor) were inoculated with R. irregularis and/or B. amyloliquefaciens in autoclaved substrates to evaluate the plant growth-promoting effects of different plant/microbe combinations under controlled conditions. The eight plant species were inoculated with R. irregularis, B. amyloliquefaciens, or both microbes or were not inoculated as a control. The impact of the microbes on the plants was evaluated by measuring dry shoot weight, colonization rate by the arbuscular mycorrhizal fungus, bacterial population density, and chlorophyll fluorescence using a plant phenotyping facility. Under dual inoculation conditions, B. amyloliquefaciens acted as a "mycorrhiza helper bacterium" to facilitate arbuscular mycorrhizal fungus colonization in all tested plants. In contrast, R. irregularis did not demonstrate reciprocal facilitation of the population density of B. amyloliquefaciens. Dual inoculation with B. amyloliquefaciens and R. irregularis resulted in the greatest increase in shoot weight and photosynthetic efficiency in T. repens and F. vesca. Peer reviewed